Pemetaan Fenologi Padi (Oryza sativa) Pada Skala Petak di Subak Dlod Sema Menggunakan Citra Satelit PlanetScope SuperDove: Phenology Mapping of Rice (Oryza sativa) at Plot Scale in Subak Dlod Sema Using PlanetScope SuperDove Satellite Imagery - Ayi Priana; I Gede Artha Sudewa Wijaya; Ardita Melani Putri; Felya Wulandari; Elsa Sinarwati; Dumaris Priskila Purba; Zulfajri; Benyamin Yosafat Manurung (Agrocentrum, 2026)
Monitoring rice growth stages in areas with small and irregular plots, such as the Subak system in Bali, requires remote sensing data with high spatial and temporal resolution. This study aims to analyze the spatial and temporal variations of rice phenology stages in Subak Dlod Sema using 3-meter resolution PlanetScope SuperDove imagery. The method involved multitemporal extraction of the Normalized Difference Vegetation Index (NDVI) to identify vegetative, generative, and ripening stages. Validation was conducted through field observations at 21 sample points for each growth stage. The results indicate that the NDVI temporal profile successfully depicts rice growth dynamics in detail, with a peak average value of 0.74 during the generative phase. Accuracy assessment showed robust results with an Overall Accuracy of 88.9%, a Kappa coefficient of 0.83, and a temporal Root Mean Square Error (RMSE) of 4.0 days during the ripening stage. Despite a slight overestimation in the generative phase due to canopy saturation, the use of PlanetScope proved highly effective in mitigating mixed-pixel issues at the individual plot scale. These findings underscore the potential of high-resolution satellites in supporting precision agriculture and planting pattern management within the Subak organization.